Pendampingan Penyusunan Visi Misi Tujuan dan Sasaran Koperasi - Adrian Maulana; Nazwa Aurellya Mulyadi; Arija Aulia Somantri (PT. Alahyan Publisher Sukabumi, 2023)
Assistance in preparing the vision. The mission, goals, and objectives of the Cooperative are one of the solutions to the problems faced by the Cirebon Millennial Saung Tani Cooperative, namely the lack of understanding of the mechanism for preparing VMTS. The purpose of this activity is to improve understanding and skills regarding the steps of preparing and determining the vision, mission, goals and objectives of the cooperative. The method of implementing this activity is mentoring carried out by modern cooperative expert assistants in 2022. The partner in this mentoring activity is the Saung Tani Millenial Cooperative, Cirebon Regency, West Java. The evaluation is carried out by looking at the percentage of completion of VMTS, where it is composed only up to the cooperative mission. So it is stated that the achievement is 50%.